The effects of digital nomads on housing affordability for local populations in Ericeira - Glaeser, Julia (2023)
The emerging number of digital nomads in recent years led to intense competition for rental accommodations between local populations and digital nomads in popular tourist destinations. This study investigates the effects of digital nomads on housing affordability for local populations in the Portuguese town Ericeira. Therefore, three focus group interviews with 17 participants divided into three interest groups (digital nomads, landlords and locals) were conducted from May to June 2022. The analysis with Leximancer software showed a semantic clustering with six important concepts that influenced housing affordability for local populations in Ericeira. The study identified that digital nomads increase the number of short-term rentals in Ericeira which makes landlords setting up higher prices benefiting from a digital nomad’s higher budget and their strong willingness to pay. As a result, digital nomads outplace local populations from the city Ericeira meaning they have a similar effect such as classic gentrification or touristification. Hence, this study contributes to ideas and concepts how to secure affordable housing options for local populations.